“We can all relate”: patient experience of an emotion-oriented group intervention after Acquired Brain Injury - Rowlands, Leanne; Salas, Christian; Coetzer, Rudi; Buckland, Sharon; Turnbull, Oliver H. (Frontiers in Psychology, 2024)
Introduction Group interventions are carried out routinely across neuropsychological rehabilitation services, to improve understanding of brain injury and aspects of impairment. Treatment provided in a group modality can bring additional perceived benefits, such as co-operative learning. However, there are very few studies which explore patient perceptions and experiences of such interventions. In the present study we investigated the experience of attending a group-based educational intervention for the consequences of acquired brain injury (ABI), which had a strong focus on emotion and emotion regulation. Methods Using qualitative semi-structured interviews (approximately 20 minutes), the study explores the lived experience of participating in the seven-session programme, the better to identify the perceived efficacy, salience and value of individual elements. Twenty participants with ABI took part in individual interviews, after completion of the group programme (the Brain Injury Solutions and Emotions Programme, BISEP). The study adopted a descriptive phenomenological philosophy, which focuses on lived experience to explore a phenomenon (i.e. the experience of BISEP). As regards methods, the study employed thematic analysis to cluster experiences into themes of meaning. Results Five themes were identified: (1) ‘Long term consequences and psychological needs’, which related to the persistent nature of direct consequences of injury and adjustment, and how these result in a need for interventions such as BISEP. (2) ‘Positive experiences of participating in the programme’, referred to participants’ overall experience of the programme and valued elements within it. The remaining themes referred to the programme as (3) a social milieu; (4) a place to learn; and (5) a place to promote positive emotional experiences. Discussion Similar to previous studies, many people reported high acceptability and perceived value of the group programme, and its role in facilitating adjustment and understanding of injury. Of particular importance was the opportunity to socialise with people who “can all relate”, in line with a growing emphasis on social rehabilitation. The findings especially highlight the relevance of emotion-focused group programmes for ABI, promoting emotion regulation, and practical tools that are delivered optimistically. Further implications for practice and future research include to focus on long term rehabilitation, a social milieu, and strategies to support adjustment.